Digiunatori e cannibali. Il rapporto tra morale e successo nella filosofia di Guido e Giorgio Voghera - Lunzer, Renate (Italogramma, 2023)
In times like ours, in the first decades of the third millennium, when violence and oppression of the weaker have become again means of politics, it seems appropriate to present considerations emerged in the first decades of the 20th century in a multicultural mitteleuropean context with a strong jewish connotation. These considerations, recorded by the Triestinian writer Giorgio Voghera in the Pamphlet postumo of 1967, are based on the ideas of his father Guido, mathematicion, inventor and umanist. They refer to the ethical anti-selection (“antiselezione etica”) on the way to success, which appears as an inversion of Hegel’s dialectics, but also of darwinistic ideologies. A bulwark against the evils of society provoked by the prepotency of the so called “spiriti acquisitativi”, who feel free of moral inhibitions in the choice of their means, can be found only in the absolut respect for the orthodoxy of means (“ortodossia dei mezzi”), i.e. often in self-limitation and voluntary.